Territorialidades camponesas e Reforma Agrária Popular em Campo do Meio-MG - Santos, Leonardo Lencioni Mattos (2023)
Despite it has been discussed in Brazil since the late 19th century, agrarian reform remains a complex and unfinished topic. Within the academy, there are several waysto analyze the experiences of agrarian reform that have occurred in the country to this day. Considering the agrarian reform projects adopted by Brazilian governments as insufficient to solve the country's agrarian problems, the Movimento dos Trabalhadores Rurais Sem Terra (Landless Rural Workers Movement - MST) beganto build a new way of thinking and doing agrarian reform. In 2007 appears for the first time in the MST documents a reference to the Reforma Agrária Popular (PopularAgrarian Reform - RAP), intended to be more than an instrument of distribution and deconcentration of land. RAP encompasses themes such as agroecology and food sovereignty, the popular action is the engine of this agrarian reform process. In this sense, in a political context of the reflux of public policies aimed at peasantry agriculture, the necessity to evaluate the project of RAP emerges from the lenses of geography analysis. Thus, it is proposed in this research to understand RAP as a model of alternative territorial development, to delimit the disputes and territorialitiesthat involve the RAP project in the Acampamento Popular Quilombo Campo Grande (Quilombo Campo Grande Popular Camp - APQCG), in Campo, do Meio, State of Minas Gerais. For this, we used secondary data from the annual reports of the DATALUTA Network, in addition to those from the research carried out under the extension program "Sowing the Earth: actions to strengthen the agroecological chain and food sovereignty in southern Minas Gerais", of which we were part. Finally, weapplied semi-structured interviews with peasants and MST leaders seeking to relate the theoretical debates about the RAP program with the practical aspects observed in the APQCG. The results indicate that RAP presents limits and possibilities forovercoming the classical paradigm of agrarian reform. From a policy idealized andcarried out by the State in the classical paradigm, RAP evolutes the role of thepeasantry in this process. This change modifies its content and its territories, bringing limits such as the lack of legal guarantee about land ownership, in the case studied,and the absence of public policies aimed at such territories. The advances concernthe model of territorial development of RAP, based on the agroecological transition and which seeks to overcome the understanding of territories in a one-dimensionalperspective, where rural spaces are seen exclusively through the productivedimension. In this sense, the multidimensionality of the RAP territories and the territorialities developed are conditions and conditioning factors of this new approach to agrarian reform in Brazil. These territorialities, such as diversified production, agroecological transition, the women's collective "Roots of the Earth" and the seedling nursery allow APQCG peasants to have their social reproduction andpolitical organization. Based on the territorialities, of which agroecological productionstands out, the MST becomes able to politically use the mediation of urban spaceand the resulting spatialities as a tool to fight for overcoming social inequalities in the Brazilian countryside and cities.